Lagenorhynchus albirostris Gray 1846 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lagenorhynchus albirostris Gray 1846 Lagenorhynchus albirostris Gray 1846, Ann. Mag. Nat. Hist., ser. 1, 17: 84. Type Locality: None given in original description, given by Gray (1846:35) as UK, England, "North Sea, coast of Norfolk.", and by Gray (1850) as Great Yarmouth. Vernacular Names: White-beaked Dolphin. Synonyms: Lagenorhynchus pseudotursio (Reichenbach 1846); Lagenorhynchus ibseni (Eschricht 1846). Distribution: North Atlantic: cold-temperate waters; L. albirostris tends to be distributed to the north of L. acutus . Conservation: CITES – Appendix II; IUCN – Lower Risk (lc). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 729, DOI: 10.5281/zenodo.7316519